Discussion of “Obfuscation in mutual funds”: The role of financial advisers - Edelen, Roger M. (Journal of Accounting and Economics, 2021)
The authors find that disclosure complexity strongly negatively relates to S&P 500 index fund returns. Because those returns are largely determined by fund fees, their evidence suggests that fund managers obfuscate to drive mutual fund investors into poor investment choices. However, the use of a passive (indexed) investment strategy can overlap with another prominent feature of the mutual fund industry: financial advisers (i.e. “money doctors,” Gennaioli et al., 2015) who assist with investment planning and implementation. The overlap can generate perverse inferences of consumer choice – seeming indifference to substantially different fees for substantially similar investments. The evidence suggests that obfuscation plays an important supporting role in the symbiosis between mutual funds and financial advisers.